Bismuth telluride topological insulator synthesized using liquid metal alloys: Test of NO2 selective sensing. (March 2021) - Mousavi, Maedehsadat; Ghasemian, Mohammad B.; Han, Jialuo; Wang, Yifang; Abbasi, Roozbeh; Yang, Jiong; Tang, Jianbo; Idrus-Saidi, Shuhada A.; Guan, Xinwei; Christoe, Michael J.; Merhebi, Salma; Zhang, Chengchen; et al.
Highlights: Nanostructured Bi2 Te3 topological insulator was proposed for NO2 gas sensing at low temperatures. Synthesis of nanostructured Bi2 Te3 was achieved benefiting from the active interfaces of liquid metals. An autogenous surface potential was detected at the interface of liquid metal (EGaIn), which was then utilized to produce the Bi2 Te3 topological insulator. With the proposed synthesis approach, the chemistry and morphology of produced materials were fine-tuned to fabricate gas sensors with optimal performance. Abstract: Nanostructured topological insulators (TIs), with high surface area and peculiar charge transport, can be advantageous for gas sensing applications. Here interfaces of liquid gallium alloys are used as reaction media to synthesize highly crystalline bismuth telluride (Bi2 Te3 ), which is a well-known TI. The synthesis via these interfaces is self-driven due to the presence of an autogenous interfacial potential on the liquid gallium-indium alloy (EGaIn). Introducing metal-based cations (Bi 3+ –HTeO2 + in acidic media) into the interfacial Helmholtz zone results in highly crystalline Bi2 Te3 platelets. Due to the non-polar surface of EGaIn liquid, the deposited films can be readily exfoliated. The films exhibit unique morphologies of nanostructured platelet-like branches. Sensors fabricated using Bi2 Te3 feature selective and sensitive nitrogen dioxide (NO2 ) physisorption at low operating temperatures. Overall, utilizing liquid metal interfaces as media to drive reactions, which take advantage of their autogenous surface potential, represents a fast and direct protocol that can be further explored to synthesize a variety of functional nanomaterials. Particularly, the approach offers an opportunity for the creation of TIs which are challenging to achieve using traditional potentiostatic methods. Graphical Abstract: Image, graphical abstract